Comparing Freedom House Democracy Scores to Alternative Indices and Testing for Political Bias: Are US Allies Rated as More Democratic by Freedom House?. Issue 4 (7th August 2016) - Steiner, Nils D.
Abstract: Several scholars have criticized the Freedom House democracy ratings as being politically biased. Do countries indeed incorrectly receive better ratings that have stronger political ties with the United States? This article tests whether differences between a number of alternative indices of democracy and the FH ratings can be explained in a systematic manner by variables that record relationships between the US and the countries under investigation. Differentiating between the periods before 1988 and after 1989, strong and consistent evidence of a substantial bias in the FH ratings is obtained for the former period. For the latter period, the estimates are less consistent, but still hint at the presence of a political bias in the FH scores.